O marketing de relacionamento como estratégia para retenção e fidelização de alunos em uma instituição de ensino de língua inglesa - Souza, Vitoria Rodrigues de (Brasil, 2024)
This study explores relationship marketing as a strategy for student retention and loyalty in an English language teaching institution. The research adopts a qualitative approach, involving the application of structured questionnaires to employees and students, as well as documentary analysis of the institution's internal records. The questionnaires, developed based on the Likert Scale, aimed to assess perceptions regarding communication, infrastructure, and service, while the documentary analysis provided complementary data on factors related to dropout and student satisfaction. Data analysis was conducted using descriptive statistical techniques, offering a detailed view of observed patterns and behaviors. The results of the research demonstrates the importance of understanding students' needs to develop strategies aligned with retention and loyalty, highlighting the relevance of integrated and personalized practices in the educational context. The contributions of this research span the social sphere, by fostering a collaborative and inclusive learning environment, and the cultural sphere, by strengthening the institution's identity and culture.